2014
DOI: 10.1586/14737140.2014.895670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lymph node dissection on the outcomes of upper tract urothelial carcinomas: a meta-analysis

Abstract: A systematic search was conducted in PubMed, Cochrane Library. 6032 patients were included. There was no significant difference in survival between LND and NLND (non-lymph node dissection) among the patients. However, the patients in the LND group had more advanced tumour stages and grades (p < 0.001). In addition, among the muscle-invasive patients, LND demonstrated remarkable CSS improvement compared with NLND (HR: 2.19; 95% CI: 1.26-3.80; p = 0.005). Moreover, subgroup analyses found that patients with musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The use of cisplatin‐based chemotherapy for high‐risk UTUC is preferable in a neoadjuvant setting because of the possible significant loss of renal function after radical nephroureterectomy (RNU), which may render a patient unfit for such chemotherapy 5 . Further, extended lymph node dissection (LND) benefits patients with locally advanced UTUC 6 . Thus, preoperative tools for predicting pathological outcomes are urgently required to identify patients with UTUC who are eligible for neoadjuvant chemotherapy (NAC), extended LND, or both.…”
Section: Introductionmentioning
confidence: 99%
“…The use of cisplatin‐based chemotherapy for high‐risk UTUC is preferable in a neoadjuvant setting because of the possible significant loss of renal function after radical nephroureterectomy (RNU), which may render a patient unfit for such chemotherapy 5 . Further, extended lymph node dissection (LND) benefits patients with locally advanced UTUC 6 . Thus, preoperative tools for predicting pathological outcomes are urgently required to identify patients with UTUC who are eligible for neoadjuvant chemotherapy (NAC), extended LND, or both.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of comparisons in previous publications are controversial (11). Yang et al (20) showed no significant difference in survival between patients with and without LND in a meta-analysis. Similarly, no significant difference was observed between the LND and no-LND groups in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…We noted the presence of cT stage heterogeneity between these two groups. Moreover, several reports have suggested that CSS is higher in patients with than without LND only among patients with muscle-invasive disease (20,21). Therefore, we carried out a subgroup analysis of patients with clinically muscleinvasive UTUC.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis on the effect of LND on outcomes of UTUC showed improved survival, particularly for locally advanced tumors. 17 …”
Section: Discussionmentioning
confidence: 99%